Quantitative Profiling of Feruloylated Arabinoxylan Side-Chains from Graminaceous Cell Walls - Schendel, Rachel R.; Meyer, Marleen R.; Bunzel, Mirko (Frontiers in Plant Science, 2016)
Graminaceous arabinoxylans are distinguished by decoration with feruloylated monosaccha-ridic and oligosaccharidic side-chains. Although it is hypothesized that structural complexity and abundance of these feruloylated arabinoxylan side-chains may contribute, among other factors, to resistance of plant cell walls to enzymatic degradation, quantitative profiling ap-proaches for these structural units in plant cell wall materials have not been described yet. Here we report the development and application of a rapid and robust method enabling the quantitative comparison of feruloylated side-chain profiles in cell wall materials following mildly acidic hydrolysis, C18-SPE, reduction under aprotic conditions, and liquid chromatog-raphy with diode-array detection/mass spectrometry (LC-DAD/MS) separation and detection. The method was applied to the insoluble fiber/cell wall materials isolated from twelve whole grains: wild rice (Zizania aquatica L.), long-grain brown rice (Oryza sativa L.), rye (Secale cereal L.), kamut (Triticum turanicum Jakubz.), wheat (Triticum aestivum L.), spelt (Triticum spelta L.), intermediate wheatgrass (Thinopyrum intermedium, maize (Zea mays L.), popcorn (Zea mays L. var. everta), oat (Avena sativa L.) (dehulled), barley (Hordeum vulgare L.) (de-hulled), and proso millet (Panicum miliaceum L.). Between 51 and 96% of the total esterified monomeric ferulates were represented in the quantified compounds captured in the feruloylat-ed side-chain profiles, which confirms the significance of these structures to the global arabi-noxylan structure in terms of quantity. The method provided new structural insights into cere-al grain arabinoxylans, in particular, that the structural moiety α-L-galactopyranosyl-(1→2)-β-D-xylopyranosyl-(1→2)-5-O-trans-feruloyl-L-arabinofuranose (FAXG), which had previous-ly only been described in maize, is ubiquitous to cereal grains.